Evaluation of equine perineural anesthesia simulators with integrated success control for veterinary education - Chodzinski, Anna; Wissing, Sandra; Tipold, Andrea; Geburek, Florian (Frontiers in Veterinary Science, 2025)
The skills necessary to perform diagnostic perineural anesthesia in equids belongs to one of the Day One Competences of a veterinarian, so every veterinary graduate should be able to perform them correctly. For logistical, hygienic and ethical reasons, practical exercises on cadaver limbs are not accessible to all students. Two equine distal limb simulators were developed and evaluated as an additional instructional tool to train the required skills. Both simulators were designed and built with an integrated success control, with Simulator I (S1) designed to be a simplified anatomical model and Simulator II (S2), a more realistic model. The simulators were tested by 68 students in the 5th year who were divided into two groups. Thirty-four students received a training session using the simplified anatomical model (S1) and the other 34 students one on cadaver limbs, the usual instructional tool. The practical learning success of both groups was validated using S2. Additionally, data on self-efficacy were collected. The results show that the two groups did not differ significantly in their practical learning success, whereas self-efficacy of both groups increased significantly after the sessions. An evaluation performed by 7 veterinarians and 49 students of the 5th year indicate that the simulators are suitable for teaching perineural anesthesia in the equine distal limb. However, S2 could be more realistic. The simulators will be used as a supplement to exercises on cadaver limbs to enable all students to practice perineural anesthesia.